Using Verbal Language for Customer Service Communication at Adira Finance Zainul Arifin Jakarta Branches - Nuryanti, Dewi (ESENSI LINGUA, 2024)
The research aimed to explain some terms of words used in verbal communication by customer service to its customers. The data were recorded data taken by recording and transcribing into utterances. The method used was the qualitative method Cresswell and the theory used for analyzing is by using Kreidler’s theory. The result found three general terms of words used in some processes. They are 1) Terms of using words in verbal communication related to service availability at Adira Finance Zainul Arifin, such as The Multipurpose credit, motorcycle/car loans, electronics, furniture, and gadget loans terms; 2) Terms of using words in verbal communication related to customer offering process such as Log in to CRM Next, choose potential leads, list of potential leads, biodata of prospective customers, and contacting prospective customers; and 3) terms of using words in verbal communication related to the credit application process, such as checking the history payment of customers, vehicle units checking, calculating credit structure, providing customers forms and files, credit analyst process, and disbursement of funds.